2006
DOI: 10.1111/j.1365-2257.2006.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

PML-RARalpha fusion gene transcripts and biological features in acute promyelocytic leukemia patients

Abstract: Acute promyelocytic leukemia (APL) is characterized by the presence of rearrangements involving the retinoic acid receptor alpha (RARalpha) gene and a variable incidence in different populations. The hybrid gene PML-RARalpha, present in 98% of cases, encodes a fusion protein essential to the pathogenesis of the disease. Depending of the PML's gene breakpoint in chromosome 15, the transcript subtypes bcr1, bcr2 and bcr3 may be formed. The correlation between these transcript subtypes and clinical parameters is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
8
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 21 publications
(26 reference statements)
7
8
0
2
Order By: Relevance
“…We have reported that APL represents 28.2% of all AML cases in centers in Brazil, a number that is very similar to the reported by Melo, R et al (28%) 13. This is ratified by information from Mexico (20%), 12 Venezuela (27.8%)14 and Peru (22%) 15.…”
Section: Apl Characteristics In Latin Americasupporting
confidence: 88%
“…We have reported that APL represents 28.2% of all AML cases in centers in Brazil, a number that is very similar to the reported by Melo, R et al (28%) 13. This is ratified by information from Mexico (20%), 12 Venezuela (27.8%)14 and Peru (22%) 15.…”
Section: Apl Characteristics In Latin Americasupporting
confidence: 88%
“…Latin Americans living in the USA have a greater frequency of APL compared to the the non-Latin American Caucasian population (i.e., 24.3 vs. 8.3% and age 31.5 vs. 46 years in Latin Americans vs. non-Latin Americans, respectively, as observed by Douer et al [31]). This finding has also been observed in other Latin American countries such as Brazil (28.2%) [32,33], Venezuela (27.8%) [34], and Peru (22%) [35]. The geographic variation suggests a possible genetic predisposition or environmental exposures to specific risk factors.…”
Section: Acute Myelogenous Leukemiasupporting
confidence: 72%
“…The confirmatory test for the diagnosis of Acute promyelocytic Leukemia is the molecular study of PML-RARᾳ i.e. t(15:17).After analysing the data 19 cases were found PML-RARᾳ positive while two cases were found PML-RARᾳ negative and also HLA-DR negative and the morphology suggest Acute promyelocytic leukemia (Fig 7 & table 7).The result of our study is similar as the study conducted by Melo RA, et al 2006 andGustavo J et al, 2002,where they found PML-RARA positive in 98% cases.…”
Section: Discussionsupporting
confidence: 86%